Analisis Komparatif Kekerasan Seksual di Sekolah Dasar: Studi Kasus di Sekolah Dasar Negeri dan Sekolah Dasar Swasta di Kota Serang - Milda Mutia Ramadhan; Fitri Pertiwi (Lembaga Yasin AlSys, 2025)
A safe, comfortable, and child-friendly school environment is mandated by national regulation, particularly UU Perlindungan Anak and Permendikbud No. 82 of 2015, yet practice on the ground continues to show vulnerability to sexual violence. This study aims to identify forms of sexual violence occurring in schools, analyze influencing factors, and examine prevention efforts already implemented. Using a qualitative case-study approach at the secondary-school level, data were collected through in-depth interviews, observation, and document analysis. The main findings indicate that in a public elementary school in Serang City, sexual violence manifests in verbal forms (taunts, sexualized language) and nonverbal forms (minor physical touching), whereas in a private elementary school verbal forms such as sexual jokes or body-related comments are more dominant; in terms of prevention, the public school conducts more frequent awareness-raising activities, while the private school emphasizes intensive supervision and parent communication; public-school policies typically reference national regulations without detailed Standard Operating Procedures (SOPs), in contrast to the private school’s more flexible internal policies that sometimes involve psychologists. External constraints, including limited parental sexual literacy, taboo norms, and weak digital supervision and internal constraints, such as children’s low knowledge and insufficient teacher training significantly hinder prevention. The study concludes that although reported cases tend to be relatively minor, schools must strengthen internal policies, build teacher capacity, and develop comprehensive child-protection systems to prevent sexual violence from an early age; the contribution lies in informing policy-oriented interventions, advancing family–school sexual literacy, and improving reporting mechanisms as strategic priorities.